Answer:
x = [tex]\frac{-6}{7+\sqrt{13}}[/tex]
r = [tex]\frac{1+\sqrt{13} }{2}[/tex]
Step-by-step explanation:
In mathematics, a geometric progression, also known as a geometric sequence, is a sequence of numbers where each term after the first is found by multiplying the previous one by a fixed, non-one number called the common ratio.
For example, the sequence 2, 6, 18, 54, ... is a geometric progression with common ratio 3. Similarly 10, 5, 2.5, 1.25, ... is a geometric sequence with common ratio 1/2.
-----
Let's take r=ratio of the geometric sequence
in first term, x is multiplied by [tex]r^{0}[/tex]
First term: x [tex]r^{0}[/tex]
Second term: 4x+3 = x [tex]r^{1}[/tex]
Third term: 7x+3 = x [tex]r^{2}[/tex]
From the last 2 equation, we have to obtain r and x values.
Second equation - First equation:
3x = x r (r - 1)
Let's state: x different from 0, so we can simplify x, obtaining:
3 = [tex]r^{2}[/tex] - r
0 = [tex]r^{2}[/tex] - r - 3
r = [tex]\frac{1+\sqrt{13} }{2}[/tex] (only the positive value of r counts)
so, going to second term of the sequence:
4x+3 = x [tex]r^{1}[/tex] => x (4 - [tex]\frac{1+\sqrt{13} }{2}[/tex] ) = -3
x ([tex]\frac{7+\sqrt{13} }{2}[/tex] ) = -3 => x = [tex]\frac{-6}{7+\sqrt{13}}[/tex]
hope it helps..